EKSPRESI MENUNJUK LOKASI OBJEK WISATA BERBASIS WRITING AS COOPERATIVE ACTIVITY OLEH MAHASISWA FAKULTAS PARIWISATA UNTRIM BALI - Mekarini, Ni Wayan (Jurnal Manajemen Pelayanan Hotel, 2021)
The study of expression to refer tourist object through writing as cooperative activity is held to identify the structure of expression since this activity gives more time to revise ideas. The idea to write based on own experience of viting object and write it with partner to open access learning together. There are 3 research questions such as form and stucture, information covers and cohesion. Data collected from general English online learning and then analyzed descriptively. To motivate the expected expression, a simple model sentence is provided. Research found out 3 conclusions. First, there are 3 categories based on form and structure chosen, such as (a) copying model in which only a few words are replaced without necessary agrement so that the expression seems similar to model. (b) Modified sentences produce additional sentence elements, for example object uniqueness and the object advantages compared to other. (c) The ability to improve is clearly found in third category where various additional information, such as attractions, photo spots, facilities, entrance tickets, to culinary delights are added. (2) The coverage of expressions includes six of the eight commonly used to refers object, i.e object name, region, theme, closest object, icon, and access. (3) The cohesion is done by cohesion tools, such as this, there, and introductory. Keywords: expression to refer tourist object, form and stucture, coverage, cohesion.